Electromagnetic and functional performance of bambuseae/MWCNT/MnFe2O4/PVA metacomposites with tunable negative permittivity for EMI shielding and flexible electronics - Reza Gholipur; Mohammad Moein Abbasi; Mahfooz Maazi (Scientific Reports)
Abstract Thorough research on materials with negative permittivity is essential to address various application scenarios and their electromagnetic interference shielding capabilities must be carefully examined. This study focuses on the development of Bambuseae/MWCNT/MnFe2O4/PVA metacomposites through a simple sol–gel method. By adjusting the multi-walled carbon nanotubes (MWCNTs) content, the permittivity of the metacomposites was altered. When the MWCNT content was at 0.064 and 0.256 g, there was a noticeable observation of negative permittivity, mainly attributed to Lorentz model. The Bambuseae/MWCNT/MnFe2O4/PVA metacomposites showcased an exceptional shielding effectiveness of − 43.2827 dB for a thickness of 1 mm. The negative permittivity led to a significant impedance mismatch, causing the metacomposite surface to reflect the majority of electromagnetic waves. Moreover, the presence of plasma oscillations and the formation of conductive networks by MWCNTs enhanced the metacomposites’ ability to absorb electromagnetic waves within the material due to their high conductivity and polarization loss. Additionally, the Bambuseae/MWCNT/MnFe2O4/PVA metacomposites displayed remarkable optical-electrical conversion and remarkable durability in the production of flexible electronic devices like light-dependent resistors, indicating their potential use in harsh working conditions.